2018
DOI: 10.1038/s41467-018-05332-z
|View full text |Cite
|
Sign up to set email alerts
|

Designing with living systems in the synthetic yeast project

Abstract: Synthetic biology is challenged by the complexity and the unpredictability of living systems. While one response to this complexity involves simplifying cells to create more fully specified systems, another approach utilizes directed evolution, releasing some control and using unpredictable change to achieve design goals. Here we discuss SCRaMbLE, employed in the synthetic yeast project, as an example of synthetic biology design through working with living systems. SCRaMbLE is a designed tool without being a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 50 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Multispecies theorists such as Despret (2004Despret ( , 2013Despret ( , 2015 and Candea (2013) have demonstrated that researchers who oblige themselves to listen and respond to non-humans, as partners in inquiry, inquire more openly; by working to generate shared concerns with these partners, they remain open to being surprised by them. While such case studies have typically focused on charismatic animals, we have observed similarly productive research participation by baker's yeast (Calvert and Szymanski 2020;Calvert 2018), andBeth Greenhough (2012) has suggested that common cold viruses and humans have participated in similar relationships. Multispecies case studies thus vividly demonstrate that RRI cannot be separated from 'the research itself' because responsiveness changes the shape of knowledge construction and constructs ethical obligations simultaneously.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Multispecies theorists such as Despret (2004Despret ( , 2013Despret ( , 2015 and Candea (2013) have demonstrated that researchers who oblige themselves to listen and respond to non-humans, as partners in inquiry, inquire more openly; by working to generate shared concerns with these partners, they remain open to being surprised by them. While such case studies have typically focused on charismatic animals, we have observed similarly productive research participation by baker's yeast (Calvert and Szymanski 2020;Calvert 2018), andBeth Greenhough (2012) has suggested that common cold viruses and humans have participated in similar relationships. Multispecies case studies thus vividly demonstrate that RRI cannot be separated from 'the research itself' because responsiveness changes the shape of knowledge construction and constructs ethical obligations simultaneously.…”
mentioning
confidence: 78%
“…In the absence of such response-abilities with other creatures, humans have no hope of being responsible to other creatures because we do not know how to listen; the stakeholder voices we hear will only ever be our own, speaking for others, and limiting possibilities to learn from and account for perspectives we might not already imagine. Developing such response-abilities might enable RRI to encompass how to care for organisms produced through science and innovation (Wickson 2016), how to care with creatures through scientific work in which they participate (Szymanski and Calvert 2018), and how to care about technoscientific futures in more-than-human ways (McLeod and Hartley 2018).…”
mentioning
confidence: 99%
“…Anonymous feedback was received from 21 of the participants and was extremely positive, with responders rating the overall course a mean average 4.6 out of 5 and particularly highlighting the breadth of techniques learnt, the relevance of the course content and the networking opportunities offered. Almost all responders believed that they would use specific techniques and skills acquired during the course in their future research and several participants have subsequently authored research articles making use of the techniques taught ( 15 , 22 , 23 ). The full responses to feedback questions are collated in Supplementary Information 3 —Anonymous Feedback Responses.…”
Section: Discussionmentioning
confidence: 99%
“…In synthetic biology, it is crucial to have a clear idea about the gene expression dynamics and population synergy. There is a deep contrast between metabolic engineering and synthetic biology [ 29 , 30 ]. In metabolic engineering, cells function as metabolic reactors, where they convert substrates into products retaining the homeostasis by replenishing the chief enzymes.…”
Section: Introductionmentioning
confidence: 99%